A study on the capacity constraint and production output at First Solar (M) Sdn Bhd / Abdul Rashid Mohd Ghazalli...[et al.] - Mohd Ghazalli, Abdul Rashid; Mohd Safie, Asrul Kamal; Zainol, Md Zahid (2019)
From operation management view, the capacity of an operation is defined as the maximum level of value-added activity that the process can achieved under normal operating conditions. More often, especially in manufacturing sector, capacity is defined as the maximum production or output rate. Despite having good capacity, the production rate / capacity are highly depending on the constraint available, which limited the company to achieve its current and future demand as well as opportunity available. In First Solar Kulim, the company is facing problem on it existing capacity. The existing production capacity is unable to manage and fulfil existing and additional demand on its solar panel. This is due to the First Solar German's factory and operation has been suspended, which had affected First Solar global production output. Increasing demand for solar panels products is another contributing factor. Without involving new investments, the problems of capacity constraints need to be addressed and resolved in order for First Solar to remain competitive in the market. In this study, the researchers have investigated on how to overcome the capacity constraints to enable First Solar Kulim to achieve its existing and future demand for its products. The researchers have focused on the process improvements at finishing area hich is the last process and become bottleneck in an existing First Solar throughput. There are four tests being conducted in order to find the best options for process improvement. All four tests have given significant results in terms of production output. However, the best option is selected based on the criteria of acceptable product quality such as panel dryness and visual specifications. This study could help to enable First Solar Kulim to manage its capacity constraints by doing a process improvement in order to achieve its maximum production output.